Teachers’ Tasks are the Change Makers in an ESL Classroom : Are you Ready? - Anil, Beena (Voices of Teachers and Teacher Educators, 2018)
Teacher’s self development programmes have become an essential component for teachers through which prospective teachers gain and prune their knowledge about teaching pedagogy and get practical exposure to convert a normal classroom into experience filled classroom for learners. All teachers have the competence to classes but how many of them can engage with the learners along with their teaching becomes a million dollar question. On the job experiences and continuous learning prepare teachers to contribute for the betterment of learners especially for primary school students. This paper focuses on the importance of teachers’ self evaluation approaches to design activities that can be used in the classroom to cater to the need of the English as a second language (ESL) learning community.